Public priorities and public goods: the drivers and responses to transitions in flood risk management - Geaves, L (2016)
This thesis examines the role of the public in Flood Risk Management (FRM) service provision at a time when the perceptions of the distribution of beneﬁts provided by FRM interventions are in ﬂux, and the role the public should play in FRM highly contested among stakeholders. Two schemes have marked the revised role of the public in FRM – Partnership Funding and Flood Re – both of which challenge existing judgments of the excludability and rivalry of beneﬁts delivered by FRM interventions. The Partnership Funding scheme allocates capital for FRM projects proportionately to the public beneﬁts they provide, allowing communities to top-up grants through local contributions. In comparison, by increasing accessibility to affordable insurance through cross-subsidies and pricing signals, Flood Re highlights a growing recognition that the distribution of gains as a result of widespread insurance uptake is greater than the beneﬁts received by the policyholder alone. Following the identiﬁcation of these schemes, we tested their social feasibility, examining both the scale and distribution of beneﬁts. Due to the different stages of implementation of each scheme at the time of writing this thesis, two distinct methods were developed. The Partnership Funding Chapter used ﬁeld data to examine how public-private funding of ﬂood defences has changed service provision and the public acceptance of this transition. Whereas the Flood Re chapter used computer-based experiments to hypothesize how Flood Re may make the purchase of insurance a more or less attractive investment for different types of consumer. We found that Partnership Funding enabled more FRM projects to go ahead, raised public awareness of ﬂood risk, and improved collaboration between stakeholders, but encouraged lower-cost projects, which, in the longer term, could transfer the expense of managing residual risk to the householder. In comparison, Flood Re provided peace of mind to householders struggling to afford rises in insurance premiums, but disproportionately beneﬁted those who annually purchased insurance. Combining this proposed inequity in Flood Re with increasing residual risks, we identify a gap in service provision for the public who cannot afford household mitigation measures. We propose that loss mitigation and ﬂood defence should become increasingly collaborative in line with the complexities of ﬂooding within a community. We seek a move away from the information asymmetry which currently exists between insurance providers and policyholders, and yet simultaneously call for local authorities to recognise the capacity of the public to participate in FRM, and sustain resilience in the face of rising ﬂood risk.